Natural pesticides: a cautionary tale - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Pesticides have their dangers but so too do natural biocontrol agents if they are used without care. Bacillus thuringiensis is a soil bacterium with enormous potential to control insect pests in a large variety of crops. With the toxins they...